PENGARUH TRUST, PERCEIVED USEFULNESS, PERCEIVED EASE OF USE, PERCEIVED RISK TERHADAP INTENTION TO USE APLIKASI INVESTASI ONLINE E-BROKERAGE - Vira Yuniar Samsul; Efraim Ferdinan Giri (Jurnal Akuntansi Dan Manajemen, 2025)
This study aims to analyze the relationship between trust, perceived usefulness, perceived ease of use, perceived risk on the intention to use e-brokerage online investment applications. This research is a primary data and uses a quantitative descriptive method with a purposive sampling method, while the data collection technique in this study uses a questionnaire survey method with 132 respondents. These respondents were taken from various people who use e-brokerage online investment applications with different characteristics of age, gender, occupation and education. The data analysis method used in this study is the Structural Equation Modeling method with the Smart Partial Lease Squares (Smart PLS) application. The results of this study indicate that perceived ease of use and perceived risk have a positive effect on the intention to use e-brokerage online investment applications, while trust and perceived usefulness have no effect on the intention to use e-brokerage online investment applications.